Biofeedback can reduce foot pressure to a safe level and without causing new at‐risk zones in patients with diabetes and peripheral neuropathy. Issue 2 (5th February 2013) - De León Rodriguez, D.; Allet, L.; Golay, A.; Philippe, J.; Assal, J.‐Ph.; Hauert, C.‐A.; Pataky, Z.
Abstract Background Plantar pressure reduction is mandatory for diabetic foot ulcer healing. Our aim was to evaluate the impact of a new walking strategy learned by biofeedback on plantar pressure distribution under both feet in patients with diabetic peripheral neuropathy. Methods Terminally augmented biofeedback has been used for foot off‐loading training in 21 patients with diabetic peripheral sensory neuropathy. The biofeedback technique was based on a subjective estimation of performance and objective visual feedback following walking sequences. The patient was considered to have learned a new walking strategy as soon as the peak plantar pressure (PPP) under the previously defined at‐risk zone was within a range of 40–80% of baseline PPP in 70% of the totality of steps and during three consecutive walking sequences. The PPP was measured by a portable in‐shoe foot pressure measurement system (PEDAR®) at baseline (T0), directly after learning (T1) and at 10‐day retention test (T2). Results The PPP under at‐risk zones decreased significantly at T1 (165 ± 9 kPa, p < 0.0001) and T2 (167 ± 11, p = 0.001), as compared with T0 (242 ± 12 kPa) without any increase of the PPP elsewhere. At the contralateral foot (not concerned by off‐loading), the PPP was slightly higher under the lateral midfoot at T1 (68 ± 8 kPa, p = 0.01) and T2 (65 ± 8 kPa, p = 0.01), as compared with T0 (58 ± 6 kPa). Conclusions The foot off‐loading by biofeedback leads to a safe and regular plantar pressure distribution without inducing any new 'at‐risk' area under both feet. Copyright © 2012 John Wiley & Sons, Ltd.